HEMATOLOGY PROFILE RATTUS NORVEGICUS THAT GIVEN INTENSIVE TRAINING AND EXTRACT OF MUSA PARADISIACA FORMATYPICA - Tangkas, Putu Jodi Wiraguna; Suarsana, Nyoman; Gunawan, I Wayan Nico Fajar (Buletin Veteriner Udayana, 2021)
Free radicals come from metabolic processes and external factors that can cause unstable blood cells. Antioxidants can protect blood cells from free radical attack, which comes from banana peels. The purpose of this study was to determine the effect of giving Musa paradisiaca formatypica to the blood profile of rattus norvegicus given intensive training. The study design uses a completely randomized design method (CRD) with a sample of 27 male Rattus norvegicus (200-225 grams/head) divided into 3 treatments, each consisting of 9 mice, namely the control group (P0), swimming group (P1), and swimming and banana extract (P2) groups for 28 days. Blood specimens taken through the orbital vein, then a complete hematological test performed to determine the hematology profile. The results showed that hemoglobin levels and total erythrocyte P1 were significantly lower (P<0.05) than controls (P0), whereas P2 was not significantly different from controls (P0). Total leukocyte cells P1 and P2 were not significantly different, but were significantly higher (P<0.05) than P0. Neutrophils and lymphocytes P1 and P2 were significantly higher (P<0.05) than P0, but eosinophils and monocytes did not differ from P0. HCT and MCHC levels P1 treatment were significantly lower (P<0.05) than controls, whereas P2 was not different from controls (P1). MCV levels of both P1 and P2 did not differ from controls (P0). From the results of this study it can be concluded, Musa paradisiaca formatypica can maintain levels of hemoglobin and erythrocytes but have not been able to maintain leukocyte levels and leukocyte differential values.